1983
DOI: 10.1128/aac.24.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Statistical comparison of the antibacterial activities of broad-spectrum penicillins against gram-negative bacilli

Abstract: Minimal inhibitory concentrations (MICs) or two a-carboxypenicillins (carbenicillin and ticarcillin) and three acylaminopenicillins (azlocillin, mezlociliin, and piperacillin) for 300 aerobic and facultative gram-negative bacilli were determined by-a microdilution method and compared by parametric statistical tests. Within each group of penicillins, MICs were highly interrelated; MICs of one antibiotic were readily predictable based on knowledge of MICs of another antibiotic. Ticarcillin was consistently more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In general, piperacillin has been the most active penicillin derivative against nonfermenters, although it was only moderately active against P. aeruginosa and A. baumannii isolates and was relatively inactive against S. maltophilia isolates (5,7,22). In the present study, it was highly active against Alcaligenes spp., B. bronchiseptica, and W. virosa; moderately active against A. baumannii, B. diminuta, B. pickettii, and Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 46%
“…In general, piperacillin has been the most active penicillin derivative against nonfermenters, although it was only moderately active against P. aeruginosa and A. baumannii isolates and was relatively inactive against S. maltophilia isolates (5,7,22). In the present study, it was highly active against Alcaligenes spp., B. bronchiseptica, and W. virosa; moderately active against A. baumannii, B. diminuta, B. pickettii, and Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 46%
“…In order to prevent hydrolysis of piperacillin by bacterial ß-lactamases, it was combined with the ß-lactamase inhibitor tazobactam, which inhibits a broad spectrum of commonly occurring plasmid-mediated ß-lactamases [6][7][8][9][10][11]. In vitro studies have demonstrated that the combination of piperacillin and tazobactam is effective against a broad spectrum of bacteria, including many members of the family Enterobacteriaceae, anaerobic species of the both cocci and bacilli and streptococcal species [12,13].…”
Section: Introductionmentioning
confidence: 99%